"Religionless" Religious Private Schools? Secularizing for the Common Good through Tuition Voucher Programs. Issue 1 (2nd January 2016) - Reichard, Joshua D.
ABSTRACT: This article is a creative application of "secularizing" for the common good to the scope and function of religious private schools. Secularizing is not secularism; in fact, it transcends both secularist and religionist ideologies. As religious private schools participate in state-funded tuition voucher programs, they can "secularize" in terms of emphasis and mission, but retain their essential religious commitments. At the same time, such "religionless" religious private schools may seek to serve public needs and solve social crises rather than to simply remain internally focused. Through participation in publically funded tuition voucher programs, religious private schools may thus become a valuable and contributing voice in the public square that is focused "outward" rather than "upward" or "inward." If religious private schools open themselves to secularizing, they can effectively partner with public school districts to meet the real and pressing needs of the community at large.